CORPORATE GOVERNANCE PRACTICES, SHARE OWNERSHIP STRUCTURE, AND SIZE ON EARNING MANAGEMENT - Hadi Sirat (Journal of Economics, Business, and Accountancy Ventura, 2012)
This study tries to analyze the effect of corporate governance practices, ownership, and firmsize on the amount of earnings management. It was conducted in the companies listed in IndonesiaStock Exchange. Ownership structure can be divided into institutional ownershipand family ownership, firm size which were measured by market capitalization. The corporategovernance practices were measured using three variables (quality audit, the proportionof independent board, and the existence of audit committee). Multiple-regression was employedfor analysis with the empirical data from 117 samples of manufacturing companieslisted in the Indonesia Stock Exchange. It was found that company size and family ownershiphave a significant influence on the amount of earnings management. The larger the company,the smaller management is on average earnings and earnings management in the firms withhigh family ownership. Those that are not a corporate conglomerate are higher than averageearnings in the management of other companies. The practice of corporate governance andinstitutional ownership variable did not have significant effect on the amount of profit madeby company management.